Thermo-physical properties of Hastelloy X and Haynes 214 close to the melting range. Issue 10 (2nd July 2020) - Ulan kyzy, Sonun; Völkl, Rainer; Munz, Oliver; Fischer, Tim; Welzenbach, Sarah; Glatzel, Uwe
ABSTRACT: The nickel-based superalloys Hastelloy X and Haynes 214 are widely used for honeycomb liners; however, thermo-physical properties at temperatures close to the melting range are poorly described in the literature. Based on the thermo-physical properties, endothermic effects between 550°C and 650°C have been observed that develop due to the formation of the short-range order in both alloys and in Haynes 214, in addition to the short-range order, an increase in the specific heat capacity due to the γ ′-precipitation up to 950° was detected. At low and intermediate temperatures, the Hastelloy X is significantly better suited than the Haynes 214. At high temperatures the Haynes 214 is superior to the Hastelloy X due to the dissolution of the γ ′-phase.